Northeast sector of the Greenland Ice Sheet to undergo the greatest inland expansion of supraglacial lakes during the 21st century. Issue 18 (23rd September 2016) - Ignéczi, Ádám; Sole, Andrew J.; Livingstone, Stephen J.; Leeson, Amber A.; Fettweis, Xavier; Selmes, Nick; Gourmelen, Noel; Briggs, Kate
Abstract: The formation and rapid drainage of supraglacial lakes (SGL) influences the mass balance and dynamics of the Greenland Ice Sheet (GrIS). Although SGLs are expected to spread inland during the 21st century due to atmospheric warming, less is known about their future spatial distribution and volume. We use GrIS surface elevation model and regional climate model outputs to show that at the end of the 21st century (2070–2099) approximately 9.8 ± 3.9 km 3 (+113% compared to 1980‐2009) and 12.6 ± 5 km 3 (+174%) of meltwater could be stored in SGLs under moderate and high representative concentration pathways (RCP 4.5 and 8.5), respectively. The largest increase is expected in the northeastern sector of the GrIS (191% in RCP 4.5 and 320% in RCP 8.5), whereas in west Greenland, where the most SGLs are currently observed, the future increase will be relatively moderate (55% in RCP 4.5 and 68% in RCP 8.5). Key Points: We present a comprehensive new data set of potential supraglacial lake locations on the Greenland Ice Sheet Supraglacial lakes are predicted to become more prevalent on the ice sheet during the 21st century with an increase in volume of 113–174% According to our results, by the end of the 21st century, the majority of supraglacial lakes will be found in northeastern Greenland